(untitled) (REMUNOM, 2024)
The cashew tree (Anacardium occidentale L.) is a tropical plant native to Brazil, widely distributed, particularly in the Northeast. The cashew is composed of a fiber-rich peduncle, often used in food, and the cashew nut, an important source of minerals. During the industrial processing of cashew for juice production, residues such as peduncle bagasse are generated. This residue is rich in fiber and has significant potential in flour form, contributing to waste reduction, minimizing environmental impacts from bagasse disposal, and enhancing the nutritional value of food products. This study aimed to develop and evaluate functional cookies formulated with cashew derivatives, specifically cashew bagasse flour (CBF) and cashew almond flour (CAF). Two formulations were prepared: F1 (with CBF) and F2 (with both CBF and CAF), by adapting a conventional recipe to partially replace wheat flour. The cookies’ characterization included physicochemical analyses to determine moisture, expansion factor, titratable acidity, yield, and crunchiness, as well as sensory analysis to evaluate the organoleptic properties such as appearance, odor, texture, and taste. The results showed that both formulations were well accepted and that, in terms of physicochemical parameters, formulation F1 presented a moisture content of 3.79 ± 0.001% and an expansion factor of 4.77 ± 0.39, while formulation F2 presented a moisture content of 3.60 ± 0.002% and an expansion factor of 4.36 ± 0.09. These values demonstrate that both formulations maintain similar texture and crunchiness characteristics. Thus, the addition of CBF and CAF resulted in good sensory acceptance and functional nutritional properties. The inclusion of CBF promotes health benefits, especially due to its fiber content and bioactive compounds, offering a promising alternative for the production of functional foods, enhancing nutritional value, and promoting sustainability.